Exploración taxonómica y de factores de virulencia en una cepa de Photorhabdus SP aislada en Costa Rica. - Monge-Cascante, Camilo (Instituto Tecnológico de Costa Rica, 2017)
The entomopathogenic bacterial genus Photorhabdus has captured interest as a biocontrol agent and producer of antimicrobial substances since it possesses a large number of virulence factors. Recently, strain P. sp. CRCIA-P01 was isolated in Costa Rica, whose description suggests it is a new species. This project aims to explore the taxonomic position of this strain and to infer its pathogenic potential through comparative genomics and identification of accessory genome elements related to virulence. The draft sequence of strain CRCIA-P01, obtained and sequenced using Illumina technology, and the complete genome sequences of reference strains P. luminescens TT01, P. asymbiotica ATCC43949 and P. temperata thracensis DSM1519 were used. Phylogenetic trees from the alignment of the sequences of recA, dnaN, gyrB and gltX genes, as well as their concatenated sequences, were generated. Genome-genome distances were calculated using GGDC. Core and accessory genome elements where identified using SPINE and AGEnt. Accessory genome elements were manually curated, putative function assigned to them, and those related with virulence, resistance or antibiotic synthesis were characterized. Dendograms generated from the alignment of recA, dnaN, gltX genes and the concatenated sequences located strain P. sp. CRCIA-P01 in the same subclade as P. luminescens TT01¸ whereas the analysis of the gyrB sequence located strain P. sp. CRCIA-P01 in the same subclade as P. temperata thracensis DSM1519. The genome-genome distance calculation results suggest that strain P. sp. CRCIA-P01 does not belong to the same species as the reference strains. The broader core genome was determined by comparing the strains CRCIA-P01 and P. luminescens TT01. Twenty-one virulence-related AGEs not shared with any of the reference strains were identified, of which 8 are specifically related to resistance. Multiple AGEs related to toxin/antitoxin systems, motility, resistance to antibiotics, etc., were found to be differentially shared among the strains involved. These results suggest that strain Photorhabdus CRCIA-P01 is a new species of the genus Photorhabdus close to P. luminescens TT01, with high pathogenic potential in eukaryotes and virulence-related AGEs that are not shared with the reference strains used.

El género bacteriano entomopatógeno Photorhabdus ha captado interés como agente biocontrolador y productor de sustancias antimicrobianas pues posee una gran cantidad de factores de virulencia. Recientemente se aisló en Costa Rica la cepa Photorhabdus sp. CRCIA-P01, cuya descripción sugiere que es una nueva especie. El presente proyecto pretende explorar la posición taxonómica de esta cepa e inferir su potencial patogénico mediante genómica comparativa e identificación de elementos del genoma accesorio relacionados con virulencia. Se utilizaron la secuencia draft de la cepa CRCIA-P01, obtenida y secuenciada con tecnología Illumina, y las secuencias de genoma completo de las cepas de referencia P. luminescens TT01, P. asymbiotica ATCC43949 y P. temperata thracensis DSM1519. Se generaron alineamientos y dendrogramas para las secuencias de los genes recA, dnaN, gyrB y gltX, y de las mismas concatenadas. Se calcularon las distancias genoma-genoma utilizando GGDC; se determinaron el genoma core y elementos del genoma accesorio usando SPINE y AGEnt. Los elementos del genoma accesorio fueron curados manualmente, se les asignó función predicha, y se caracterizaron aquellos relacionados con virulencia, resistencia o síntesis de antibióticos. Dendogramas generados a partir de los alineamientos de los genes recA, dnaN, gltX y las secuencias concatenadas ubicaron a la cepa P. sp. CRCIA-P01 en el mismo subclado que P. luminescens TT01, mientras que el análisis de la secuencia de gyrB ubicó a la cepa P. sp. CRCIA-P01 en el mismo subclado que P. temperata thracensis DSM1519. El cálculo de la distancia genoma-genoma sugiere que la cepa P. sp. CRCIA-P01 no pertenece a las mismas especies que las cepas de referencia. El genoma core más amplio se determinó al comparar la cepa CRCIA-P01 con P. luminescens TT01. Se identificaron 21 AGEs relacionados con virulencia no compartidos con ninguna de las cepas de referencia, de los cuales 8 se relacionan específicamente con resistencia. Se identificaron además múltiples elementos relacionados con sistemas toxina/antitoxina, motilidad, resistencia a antibióticos, etc., diferencialmente compartidos entre las cepas involucradas. Estos resultados sugieren que la cepa Photorhabdus sp. CRCIA-P01 es una nueva especie del género Photorhabdus cercana a P. luminescens, con alto potencial patogénico en eucariotas y AGEs relacionados con virulencia que no se comparten con las cepas de referencia utilizadas.
Proyecto de Graduación (Licenciatura en Ingeniería en Biotecnología) Instituto Tecnológico de Costa Rica, Escuela de Biología, 2017.
Keywords: Photorhabdus; Virulencia; Genómica comparativa; Taxonomía; CRCIA-P01